The Implementation Of Teaching Writing To The Seventh Grade Student Of Smp Muhammadiyah 4 Surakarta In 2015/2016 Academic Year - Ayu Maghrita, Rifka, Mauly Halwat Hikmat,Ph.D, Nur Hidayat,M.Pd (2017)
The research investigates the implementation of teaching writing to the seventh grade student of SMP Muhammadiyah 4 Surakarta. The study aims at decribing (1) the implementation of teaching writing and (2) the problems faced by the students at the seventh grade of SMP 4 Muhammadiyah Surakarta in 2015/2016 academic year. This Research is qualitative research. The subject of the study is seventh grade student of SMP Muhammadiyah 4 Surakarta. The data are in the form of information related to implementation of teaching writing at the seventh grade students of SMP Muhammadiyah 4 Surakarta year 2016 that have been collected from observation and interview. Methods of collecting data are observation, interview, and document analysis. The techniques for analyzing data are data reduction, data source, conclusion and verification. The result of the analysis shows that objectives are divided into two kinds, there are general learning objective and specific learning objective.The materials used by the teacher and the students are handbook for seventh grade students. The procedures are pre-teaching, while teaching and post teaching. The problems faced by the teacher in implementing the teaching writing are lack of media, and different capability of the students and lack of the motivation from the teacher. Keyword: implementation, teaching, writing